Arabic Literature as a Mirror of Its Era: A Historical Study from the Jahiliyyah Period to the Peak of Islamic Civilization - Alam, Fajar Nur Syah; Sabahah Yumna (IJAS: International Journal of Arabic Studies, 2025)
Arabic literature is the most authentic reflection of the social, cultural, and political dynamics that have shaped the Arab world from the pre-Islamic era (Jahiliyyah) to the peak of Islamic civilization. This article examines the historical development of Arabic literature by highlighting the shifts in themes, forms, and functions of literature within the context of Arab societal changes.During the Jahiliyyah period, poetry served as the primary medium for expressing tribal identity, pride, and collective existence. With the advent of Islam, literature underwent a major transformation with the revelation of the Qur’an, which not only altered the structure of language and rhetoric but also expanded the intellectual horizons of Arab society.This evolution reached its peak during the Abbasid era, when literature flourished as a vehicle for intellectualism, social critique, and philosophical exploration, alongside the advancement of knowledge centers such as Baghdad.This study employs historical-philosophical and philological approaches to demonstrate that Arabic literature is not merely a cultural product, but also an agent of civilizational change. By viewing literature as a mirror of its era, this article underscores the importance of understanding literary works as an integral part of the history of Islamic civilization.